Pengaruh Return on Asset, Earning per Share dan Price to Book Value terhadap Harga Saham: Studi Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia - Maria Beatrixon Sapta; Gendro Wiyono; Risal Rinofah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to examine the effect of Return On Assets (ROA), Earning Per Share (EPS) and Price To Book Value (PBV) on stock prices. The research took samples of LQ45 companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling. This purposive sampling method is a sample selection method based on predetermined population characteristics. The sample in this study is 32 LQ45 companies listed on the Indonesia Stock Exchange in 2016-2020. In research using secondary data sources in the form of financial reports. While the data collection method used is the collection technique. In this study, the data analysis technique used was multiple linear analysis supported by the classical assumption test. The results of this study are that Return On Assets (ROA) has a negative and insignificant effect on stock prices, Earning Per Share (EPS) has a positive and significant effect on stock prices, Price To Book Value (PBV) has a negative and insignificant effect on stock prices. So the conclusion is that Earning Per Share (EPS) has a positive and significant effect on stock prices, while Return On Assets (ROA) and Price To Book Value (PBV) have a negative or insignificant effect on stock prices. Keywords: Return On Assets (ROA), Earning Per Share (EPS), Price To Book Value (PBV), Stock Price